A COMPARATIVE-TYPOLOGICAL STUDY OF THE NUMBER CATEGORY IN UZBEK AND ENGLISH LANGUAGES - Mengniyazova Gulnora Toshtemirovna (Scholar Express Journal, 2024)
This paper conducts a comparative-typological analysis of the number category in Uzbek and English languages. It explores various aspects such as singular vs. plural forms, agreement with numerals, presence of a dual number, and strategies for expressing collective and partitive meanings. The study reveals shared patterns and unique features, providing insights into how languages encode numerical concepts and highlighting the richness of linguistic diversity
Keywords: linguistic; Uzbek; comparative; analysis